EXPECTATIONS AND SATISFACTIONS OF BANGKOK BASKETBALL COURT USERS TOWARDS SPORT FACILITIES PROVIDED AT BASKETBALL COURT - Sanguansap, Sitthinon; Pookaiyaudom, Gulapish (Journal of Sports Science and Health, 2023)
Purpose: The purpose of this research was to study the relationship and to compare the expectations and satisfaction of Bangkok basketball court users towards sport facilities provided at basketball court in Bangkok. Methods: The sample was 385 people who used basketball courts under the supervision of Culture, Sports and Tourism Department at least 5 times/month in Bangkok, using online questionnaires through Google Form as a tool for data collection. The Google Form was sent as the links to 8 Facebook pages of sports centers and youth centers. The index of correspondence between the question and the objective. It was found that the values obtained were between 0.80-1.00 and the reliability of the questionnaire obtained was 0.93. Data were analyzed using basic statistics, namely frequency, percentage, mean score. and standard deviation Statistics for hypothesis testing The statistical t-test was used for mean estimation, with the level of statistical significance set at 0.05, and Pearson’s correlation analysis was used. Results: It was found that the expectation of the core product, other facilities, services personal. There was a difference in satisfaction of Bangkok basketball court users towards sport facilities provided at basketball court in Bangkok in all aspects. with a statistical significance of 0.05. Expectations were positively related to satisfaction of Bangkok basketball court users towards sport facilities provided at basketball court in Bangkok in all aspects. Conclusion: the expectations and satisfaction of Bangkok basketball court users towards sport facilities provided at basketball court in Bangkok. They were positively correlated and were significantly different at the 0.05 level.